ANALYSIS AND DESIGN OF CONCEPTUAL MODELS OF DATA WAREHOUSE IN ARISTY WEDDING ORGANIZER - Isni Oktria; Dyah Cita Irawati (Asosiasi Dosen Muda Indonesia, 2023)
Wedding Organizer is a business that specializes in services that specifically help the bride and groom and families in the planning and supervision of the implementation of a series of events into a wedding party. The necessity of designing a conceptual model of data warehouse on a wedding organizer devoted to designing the model and the data flow that existed at the wedding organizer. The data warehouse is a collection of data from various sources placed together in a safae place for querying and reporting processes. The conceptual model of the data warehouse is a logic design that represents the data. Data warehouse design method used in the study is the dimensional data modeling Powell. The study resulted in the design of data into multiple tables then the tables is determined which inculeds the dimension tables and fact. The identification process is intended to design a star schema, snowflake schemas, and the fact constellation schema of existing data on the wedding organizer CV . Aristy so that in the future can be created a wedding organizer information system for CV. Aristy